Makna Gramatikal Verba dalam Lirik Lagu Hoshi wo Tsukame dan Garuda to Tomo ni oleh Hiroaki Kato - Nugroho, Rahadiyan Duwi; Wulandari, Siti; Zuliastutik, Hendri; Pratama, Adi Putra (AYUMI : Jurnal Budaya, Bahasa dan Sastra, 2023)
The problem of this research is how the influence of verbs that have grammatical meaning in the lyrics of the songs Hoshi wo Tsukame and Garuda to Tomo ni affects the meaning of the two songs. The theories used in this research are semantic theory (imiron), grammatical meaning (bunpouteki-imi), imperative verbs (meireikei), …n desu verbs, and uncertain verbs (doushi no futeikei). The aim of this research is to determine changes in the grammatical meaning of the verbs in the lyrics of the songs Hoshi wo Tsukame and Garuda to Tomo ni, secondly, to find out the influence of these verb changes in influencing the meaning of the two songs. The benefit of this research is that Japanese language learners can understand that changes in the grammatical meaning of Japanese verbs in Japanese song lyrics can influence changes in meaning. The research method in this research is descriptive qualitative. The results of this research are that the verb (doushi) underwent a process of changing its lexical to grammatical meaning as many as 9 data. First, there are two forms of command verbs (meireikei). One, verb + form ...ro (ーろ) found 4 verbs, namely, misetsukero ‘show me’, yakitsukero ‘note it’, koero ‘go beyond’, oitsuzukero ‘keep pursuing’. Two, verb + form...ge (ーげ) were found 3, namely, tsunage ‘join hands’, tsudoe ‘gather’, tachimukae ‘face’. Second, the verb form ...n desu with the form: verb + form ...nda (ーんだ) was found 1, namely, shinjiru nda. ‘trust me’. Third, an indefinite verb (doushi no futeikei) with the form: verb + form...zuni (ーずに) was found 1, namely, akiramezuni ‘without giving up’. These three verb functions indirectly influence the meaning content of the two songs which call for, strengthen and provide an optimistic attitude for athletes, especially the Indonesian Team and the U17 National Team, to fight persistently, never give up and believe they can achieve the best achievements. Keywords: Garuda to Tomo ni; grammatical meaning; Hoshi wo Tsukame; song lyrics; verb.